2020
DOI: 10.32598/cmja.10.1.866.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Self-Care Education on the Care Burden of Mothers With Children Hospitalized in Intensive Care Units for Open Heart Surgery

Abstract: Objective: Spiritual health of caregivers has association with the patients’ health, but less attention has been paid to spiritual self-care education in health programs. This study aimed to assess the effect of spiritual self-care education on the care burden of mothers with children in hospitalized in Intensive Care Units (ICUs) for open heart surgery. Methods: This quasi-experimental study was conducted on 60 mothers of children hospitalized in ICUs of Shahid Modarres Hospital in Tehran, Iran. They were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In a study on the effect of group training on the caregiver burden of caregivers of cancer children, Ali Akbarian et al ( 2019) reported that group training empowers parents to take care of their children, which in turn reduces the caregiver burden of these caregivers (14). In a study of the effect of spiritual self-care training on the caregiver burden of mothers of children undergoing heart surgery in pediatric cardiac intensive care unit, Delir et al ( 2019) showed that spiritual self-care training reduces the caregiver burden in mothers of children undergoing heart surgery (15), and both studies are consistent with the present study. In a study of the perceived stress and caregiver burden in elderly caregivers: the moderating role of resilience, Jafari et al (2022) showed that elderly caregivers experience a moderate to high caregiver burden (35).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a study on the effect of group training on the caregiver burden of caregivers of cancer children, Ali Akbarian et al ( 2019) reported that group training empowers parents to take care of their children, which in turn reduces the caregiver burden of these caregivers (14). In a study of the effect of spiritual self-care training on the caregiver burden of mothers of children undergoing heart surgery in pediatric cardiac intensive care unit, Delir et al ( 2019) showed that spiritual self-care training reduces the caregiver burden in mothers of children undergoing heart surgery (15), and both studies are consistent with the present study. In a study of the perceived stress and caregiver burden in elderly caregivers: the moderating role of resilience, Jafari et al (2022) showed that elderly caregivers experience a moderate to high caregiver burden (35).…”
Section: Discussionsupporting
confidence: 88%
“…Pressure or caregiver burden describes the physical, psychological, socioeconomic reactions that are imposed on the caregiver during the care of the patient (14). In fact, caregiver burden is a type of continuous tension or negative experience caused by patient care, which causes a decrease in the physical and mental health of the caregiver (14,15). The increased caregiver burden in caregivers causes changes in their lifestyle and subsequent consequences such as inadequate patient care, patient abandonment, family isolation, weaker performance, decreased well-being, decreased self-control, more psycho-social stress, being frustrated from social support, disrupted family relationships, all of which reduce the quality of life of caregivers and even patients themselves (16,17).…”
mentioning
confidence: 99%
“…The results of some similar studies align with the present study's findings. Dalir et al examined the effect of spiritual self-care training on the care burden of mothers with children hospitalized in intensive care units for open heart surgery (21). The amount of care burden on caregivers was high.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of care burden on caregivers was high. After training in spiritual self-care, the care burden of caregivers decreased to a moderate level (21). Bamari et al evaluated caregivers' burden of patients with type 2 diabetes referred to a diabetes clinic in Zabol, Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The data analysis results also con rmed such a relationship. On the other hand, the high number of chemotherapy sessions can be attributed to the severity of the disease and that the mother would be able to accompany the child to perform chemotherapy with more ability due to understanding the severity of the disease [42,43].…”
Section: Discussionmentioning
confidence: 99%